The early years of inflation targeting: Review and outlook - Andreas Billmeier (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1999)
This paper deals with a 'new' type of monetary policy making: Inflation Targeting (IT). It attempts to identify reasons for which countries might be inclined to adopt this framework for monetary policy. By reviewing recent experience of inflation targeting countries, the paper outlines the major operational arguments regarding the implementation of IT. Another important issue is the applicability of IT in transition countries: in the light of EU (and, in the longer run, EMU) accession, Inflation Targeting might be an interesting policy framework to at least some countries in Central and Eastern Europe.
Keywords: E52; E58; P24; 330; inflation targeting; monetary policy; Central and Eastern Europe; Inflation Targeting; Inflationsbekämpfung; Theorie; Welt; Osteuropa